Ocena atrakcyjności inwestycyjnej gmin województwa warmińsko-mazurskiego i sposoby jej poprawy w opinii władz lokalnych - Lizińska, Wiesława (The Assessment of Investments Attractiveness of Communes in Warmia and Mazury Region and Ways of Its Improvement in Opinion of Local Authorities, 2009)
The purpose of the study was to estimate the investments attractiveness of communes in Warmia and Mazury region and the factors influencing this state and also to indicate the instruments causing its improvement. Local authorities that had participated in a survey (78) described their communes as attractive and quite attractive (86.5%). The main factors determining the level of attractiveness are location (4.17 on 1-5 scale) and territorial development for investment (4.02). To improve the commune's investments attractiveness local authorities mostly protect the environment (22.31%) and provide high quality and efficiency of services in their offices (21.07%) (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 716-723